Ovarian Failure Induced Labial Adhesion after Hematopoietic Stem Cell Transplantation - Mustafa Ulubay; Ugur Keskin; Ulas Fidan; Fahri Burcin Firatligil; Riza Efendi Karaca; Mustafa Ozturk; ibrahim Eker; ibrahim Alanbay; Ali Ergun (Çukurova Üniversitesi Tıp Fakültesi Dergisi, 2015)
Labial adhesion is a disease which occurs after complete or partial fusion of labium majors and / or minors. It usually originates at the posterior fourchette and sometimes progresses towards urethral opening and clitoris. Incidence of labial adhesion is most frequent in prepubescent girls with a peak incidence at the age of 13 and ndash; 23 months. The factors that cause labial adhesion remain unknown. Vaginal irritation or inflammation process with underlying hypoestrogenism can cause this disease.We present a case who developed labial adhesion due to ovarian failure after hematopoietic stem cell transplantation. [Cukurova Med J 2015; 40(3.000): 588-592]